Management Interventions: Are They Feasible in Arid Zone Livestock Pro-duction Systems - Squires, V R; Andrew, M H (Annals of Arid Zone, 2016)
Management interventions in arid zone livestock production systems have generally failed to provide long term improvement in sustainability. The reasons for this are discussed. The differences between livestock production systems and rangeland development are also discussed and the management implications elaborated. The importance of a participatory approach to improvement of livestock-based systems in the arid zone is emphasized. This paper reviews the recent history of pastoral production systems and considers the prospects for successful management interventions in the light of the constraints under which they operate and the effect of the shift, in almost all of the world's pastoral regions, to a cash or market economy. By drawing on the mistakes of the past and putting technology in the context of people's real needs, our thinking is on track to produce some really effective solutions.